Pengaruh Substitusi Tepung Daging Ikan Gabus (Ophiocephalus Striatus) Terhadap Nilai Proksimat Dan Tensile Strength Mi Kering - Anggarini, Novi Hidayah; , Eni Purwani, S.Si., M.Si; , Fitriana Mustikaningrum, S.Gz, M.Sc (2015)
Background: Noodle is a favorite food product for all people because had a lot of taste, texture and interesting type, low price and easy to cook. Snakehead fish contains good quality protein with high albumen and completely amino acid, so that it potential to be functional product. Noodle processing with fish meal snakehead powder substitution will influence proximate and tensile strength of dried noodle. Objective: The aim of the study was to determine the effect of fish meal snakehead powder substitution with proximate value and tensile strength of dried noodle. Research Method: This research was used experimental method with completely randomized design with four different treatments of substituted (0%, 5%, 10% and 15%). Statistic analyze was used one way anova with significant value 95% and continued with Duncan Multiple Range Test. Result and Discussion: The data shown that, water content was between 8,55%-9,32%, ash content was 1,14%-2,17%, fat content was 0,52%-0,91%, protein content was 13,83%-25,79% and carbohydrate content was 62,89%-75,39%. Substitution 0% gave the highest tensile strength value of noodle there according to 0,29 N.Meanwhile, substitution 15% gave the lowest tensile strength value there with 0,23 N. Conclusion: All in all, the substitution of fish meal snakehead powder had effect on the proximate value (water, ash, fat and protein) with sig.= 0,000 (p<0,05), while there is no relationship with tensile strength of dried noodle sig.= 0,061 (p>0,05). Suggestion: According to proximate value and tensile strength, the 15% substitution of snakehead fish powder was good to use in dried noodle product. Keyword : Fish meal snakehead powder, Proximate Value, Tensile Strength, Dried Noodle. Bibliography : 54: 1975 - 2014.